Anatomopathological alteration and serum and urinary biochemical parameters in dogs with diagnosis of Dioctophyme renale (Research, Society and Development, 2022)
Many animals affected by Dioctophyme. renale are asymptomatic and the definitive diagnosis is images diagnosis and anatomopathological examination. This study describes the biochemical parameters of blood and urine and anatomopathological exams of 15 dogs diagnosed with D. renale in the region of Pelotas-Rio Grande do Sul. Data from anamnesis and serological and urinary laboratory tests were obtained from animal care protocols at the Hospital de Clínicas Veterinárias, Faculdade de Veterinária da Universidade Federal de Pelotas, and anatomopathological analyzes by the Oncology Service -SOVET-UFPEL. Macroscopic changes were observed in all samples, with renal parenchyma atrophy and capsule thickening being the most frequent. The histopathological examination revealed replacement of the renal tissue by fibrosis, glomerulosclerosis and eventually the presence of parasite eggs. Regarding blood and urinary parameters, only one of the animals showed changes in the reference values ​​of serum urea and all of them had creatinine within the parameters considered normal. Urinalysis showed the presence of proteins, occult blood, granular casts, crystals and parasite eggs. Statistical tests showed a correlation between the evolution and degree of renal lesions with altered parameters, but even in dogs that presented lesions of acute renal failure (ARF), there were concomitant lesions of chronic renal failure (CRF). It was possible to conclude that serum and urinary parameters alone do not reflect the real impairment of the affected kidney, but associated with the degree of kidney injury are allies for a better staging of the affected animals.